Fatty acid composition of the porcine conceptus in response to maternal omega-3 fatty acid supplementation - A B Brazle; B J Johnson; Evan C Titgemeyer; S K Webel; Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 2005)
Marine and plant sources of omega-3 fatty acids have been evaluated for their effects on reproductive and other traits. Therefore we evaluated the effects of two sources of polyunsaturated fatty acids on the composition of the pig endometrium and conceptus. Treatments were Control, a corn-soybean meal diet; Flax, Control diet plus ground flax (3.75% of the diet); and PFA, Control plus a protected marine source of polyunsaturated omega-3 fatty acids (FertiliumÂ®, 1.5% of diet). Supplements replaced equal parts of corn and soybean meal in the PFA and Flax diets. Dietary treatments did not affect linoleic acid, linolenic, and arachidonic acid concentrations in conceptuses, but Flax increased (P = 0.055) eicosopentanoic acid (EPA) 78.8% and docosopentanoic acid (DPA) 32% (P<0.05) in the fetus. Gilts receiving PFA had 16% more (P<0.006) docosohexanoic acid (DHA) in their fetuses than fetuses in Controls had. Both Flax and PFA diets increased (P<0.05) DHA in the chorioallantois. In the endometrium, both EPA and DPA were increased (P<0.02) by the Flax diet, whereas the gilts receiving PFA had increased DHA (P<0.0001). In summary, initiating fatty acid supplementation approximately 40 d before breeding with these omega-3 supplements affected conceptus and endometrial composition early in the fetal period of pregnancy. Further, plant and marine sources affected fatty acid composition differently. These differences may have implications for the physiological responses reported in the literature.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Embryo; Pigs; Omega-3 fatty acids; Swine